ҚАРАҚАЛПАҚ ХАЛЫҚ ЕРТЕКЛЕРИ ТИЛИНДЕ ДИАЛЕКТИЗМЛЕРДИҢ БЕРИЛИЎИ - Кунназарова, Ш.М. (FAN va JAMIYAT, 2018)
The article is devoted to the issues of using dialecticisms in the language of Karakalpak folk fairy tales. According to the opinion of some scholars- dialectologists dialectal words may be divided into the following groups: lexico-phonetic, lexico-grammatical and lexical groups. They have been shown with examples, and the borders of their usage were defined.